One new species of the genus Neotriplax (Coleoptera: Erotylidae) from China - Li, Jing; Ren, Guo-Dong; Dong, Jian-Zhen (Zootaxa, 2006)
One new species of the genus Neotriplax Lewis (Coleoptera: Erotylidae), N. minima sp. nov., from China is described in this paper. It can be distinguished from N. arisana Miwa by body length less than 4.0mm, head black with basal area brown, sparsely punctured; posterior border of pronotum strongly narrowed backwards, with a narrow lobe in the middle. Compound eye, stridulatory file, terminal segment of antenna and maxillary palpus are illustrated as scanning electron micrographs. Type specimens are deposited in the Museum of Hebei University, China.